The effect of sales promotion, shopping lifestyle, hedonic shopping motivation, and customer engagement on impulse buying on online marketplace consumers - Harsilla Tiana Devino; Yunita Engriani (Universitas Negeri Padang, 2023)
The purpose of this study was to determine the effect of Sales Promotion, Shopping Lifestyle, Hedonic Shopping Motivation, and Customer Engagement on Impulse Buying for Shopee consumers. The population in this study is all people who have made purchases at Shopee. The sampling technique used was the purposive sampling technique. The sample in this study amounted to 250 respondents. Data collection was carried out by distributing questionnaires. Research data were analyzed using SEM analysis with SmartPLS version 3.7 software. The results of this study indicate that Sales Promotion and Hedonic Shopping Motivation have a positive and insignificant effect on Impulse Buying, while Shopping Lifestyle and Customer Engagement have a positive and significant effect on Impulse Buying.